Alternative Strategies to Avoid Layoff in Airlines Industry During the Covid-19 Pandemic - Singh, Padmalini; D, Dilip; P, Nuthan Jeevraj; Hung, Yip Wei; Kee, Daisy Mui Hung; Wen, Yap Sing; Pandey, Divya; Pandey, Rudresh; Yunn, Sek Yuen; Wen, Shelly Foo Hui (International Journal of Tourism and Hospitality in Asia Pasific, 2021)
This research was carried out to explore the layoff situation among the Airline industry during the COVID-19 pandemic and suggest the alternative strategies that would consider by the Airline company. The method used in this research is an online questionnaire distributed to 100 respondents as the primary data collection and the secondary data analysis from the empirical studies that can obtain from electronic and non-electronic media. The findings of this research indicated that one of the suggested alternative strategies, Furlough, is the most recommended one. However, Attrition and Hiring Freeze strategy has less recommended because of the low effectiveness of this strategy on downsizing companies. The study enables the airline company to consider the alternative strategies on their downsizing policy in order to minimize the employees and company loss.